Clinical characteristics of patients with chronic post-traumatic pain: data from a prospective study - A. A. Bialik; A. E. Karateev; M. A. Makarov; V. А. Nesterenko; V. E. Bialik; E. I. Bialik (Современная ревматология, 2024)
Chronic post-traumatic pain (CPTP) is diagnosed when pain persists for ≥3 months after injury. This is a serious condition that significantly limits patients' quality of life and ability to work and is one of the predictors of the development of post-traumatic osteoarthritis.Objective. To investigate the clinical features of CPTP after knee injury.Material and methods. The study group comprised 103 patients (mean age 39.4±12.5 years, 51.5% women). All patients had a knee injury with diagnosed involvement of the anterior cruciate ligament and/or meniscus and suffered from pain ≥1 month after the injury ≥4 points on the numerical rating scale (NRS, 0–10). Patients were assessed after 3 and 6 months. Pain intensity during movement, at rest and at night and functional impairment were assessed using NRS. KOOS, EQ-5D, PainDETECT, CSI, Pain Catastrophizing, HADS, FIRST and FACIT questionnaires.Results and discussion. After 3 months, the number of patients with CPTP was 33 (32.0%). After 6 months, these patients had significantly more severe symptoms than patients with knee injuries without CPTP (control group, n=70). In the CPTP and control groups, the median pain during movement was 5.0 [4.0; 6.0] and 1.0 [0.0; 1.0] respectively, p12 was found in 24.2 and 2.9% of cases, p <0.001 ; pain at rest – 2.0 [2.0; 3.0] and 0.0 [0.0; 1.0], p <0.001 <0.001;; pain at night – 2.0 [1.0; 3.0] and 0.0 [0.0; 0.0], p <0.001; KOOS score – 4.0 [1.0; 5.5] and 2.0 [1.0; 3.5], p <0.001; quality of life according to EQ-5D – 0.65 [0.52; 0.73] and 0.89 [0.69; 1.0], p <0.001; according to EQ-5D scale – 64.0 [50.0; 70.0] and 80.0 [70.0; 90.0], p <0.001 ; a PainDETECT score of >12 was found in 24.2 and 2.9% of cases, p< 0.0037; according to HADS, depression ≥11 – in 21.2 and 2.9%, p< 0.001, according to HADS, anxiety ≥11 – in 24.2 and 4.3%, p=0.0038; CSI ≥40 – in 9.0 and 0%, p=0.03; pain catastrophizing ≥30 – in 12.1 and 0%, p=0.005; FIRST ≥5 – in 6.1 and 0%, p=0.358; FACIT <30 – in 15.2 and 2.9%, p=0.004. After 6 months, statistically significant differences were found between the CPTP group and the control group in all sections of KOOS questionnaire (p <0.001 for all parameters).Conclusion. Three months after knee injury, 32.0% of patients developed CPTP. All had moderate/severe pain with impaired function and reduced quality of life, one in five patients had symptoms of neuropathic pain, signs of depression and anxiety. Patients with CPTP showed significant changes in all sections of KOOS questionnaire.